Rhetoric in Homer? An Analysis of Odysseus’ Supplication to Nausicaa in Odyssey 6 (135-97) (Nuntius Antiquus, 2020)
This article discusses the possibility of exploring the field of rhetoric within the Homeric poems. Is it adequate to employ the term “rhetoric” in discussions of Homeric poetry? We contend, following Knudsen (2014), that yes, the Iliad and the Odyssey provide us with the earliest instances of rhetorical activity in Antiquity. Firstly, we address why some scholars disregard that possibility, then argue why we disagree with them. Finally, we apply the elements of our theoretical discussion to an analysis of Odysseus’ supplication to Nausicaa in Odyssey 6, focusing on: a) the introduction by the Homeric narrator with the terms kerdíon, kerdaléos, and meilíkhios; and b) Odysseus’ strategic speaking when trying to convince Nausicaa to provide him with clothes and information about the way to town.